واقع الإبداع الإداري ومعوقاته لدى مديري المدارس في مرحلة التعليم الأساسي بمحافظة دمشق - سليمان, جمال; خليل, بلسم (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف لواقع الإبداع الإداري ومعوقاته التي تواجه مديري المدارس في مرحلة التعليم الأساسي بمحافظة دمشق من وجهة نظرهم بالإضافة إلى مقترحاتهم في هذا الشأن. قامت الباحثة بالاعتماد على الأدب النظري والدراسات السابقة في مجال الإبداع والإدارة المدرسية لوضع أداة الدراسة حول درجة تطبيق أسلوب الإبداع الإداري ومعوقاته وفق المجالات (الإمكانيات البشرية، الإمكانيات المادية، الإمكانيات المعنوية، إمكانيات المجتمع المحلي، إمكانيات الوزارة ومديريات التربية وكليات التربية)، وتكونت الاستبانة في صيغتها النهائية من (68) بنداً حول واقع الإبداع الإداري ومعوقاته في المدارس، وأجريت الدراسة على عينة تكوّنت من (46) مديراً ومديرة من مدارس مرحلة التعليم الأساسي الحلقة الأولى في محافظة دمشق. وقد أظهرت نتائج الدراسة وجود معوقات تواجه تطبيق أسلوب الإبداع الإداري في المدارس، وتعيق تطوير العملية التربوية عامة والعمل الإداري خاصة وتحول دون زيادة مستوى الإبداع الإداري لدى العاملين في المدارس من وجهة نظر مديريها ومن هذه المعوقات (المركزية الإدارية، ضعف العمل الجماعي، ضعف التأهيل والتدريب، قلة الحوافز المادية والمعنوية...). ولم تظهر نتائج الدراسة فروق ذات دلالة إحصائية عند مستوى دلالة (5%) من وجهة نظر المديرين لدرجة تطبيق أسلوب الإبداع الإداري لمتغير الجنس ومتغير المؤهل العلمي في مدارس التعليم الأساسي الحلقة الأولى في محافظة دمشق في كل مجالات الدراسة. وقد تضمنت الدراسة بعض التوصيات التي يمكن أن تكون عون وفائدة في رفع مستوى تطبيق أسلوب الإبداع الإداري ومواجهة المشكلات التي يمكن أن تعوق تطبيقه من أجل الرقي بالعملية التربوية. This study aimed to identify the reality of creativity and administrative constraints faced by school administrators at the stage of basic education in Damascus City from their point of view in addition to the suggestions in this regard. The researcher depended on literature theory and previous studies in the field of creativity and school administration to develop a tool to study the degree of applying the method of creativity and administrative constraints according to these areas: (human capabilities, financial resources, the moral potential, potential of the local community, the possibilities of ministry and the departments of Education and colleges of education), and the resolution consisted in its final form of (68) items on the reality of creativity and administrative constraints in the schools, and the study was conducted on a sample of (46) directors and directresses of schools for basic education, the first cycle in the province of Damascus. The results of the study show constraints facing the application method of innovation management in schools, hindering the development of the educational process in general and administrative work in particular and obstructing any increase in the level of innovation management in working in schools from the perspective of managers, and these constraints are the central management, poor teamwork, poor rehabilitation and training, lack of material and moral incentives .... Results of the study did not show statistically significant differences at the level of significance (5%) from the viewpoint of managers of the extent of the application of innovation management style to the variable sex and qualification variable in the schools of basic education, the first cycle in the province of Damascus in all fields of study. The study included some recommendations that can help and be useful in raising the level of application of the administrative and creative way of facing the problems that can hinder its application in order to upgrade the educational process.